Terahertz transmission control using polarization-independent metamaterials - Lee, Sang-Hun; Lee, Dong-Kyu; Kim, Chulki; Jhon, Young Min; Son, Joo-Hiuk; Seo, Minah (OPTICAL SOC AMER, 2017)
We present terahertz (THz) transmission control by several uniquely designed patterns of nano-slot antenna array. Collinearly aligned slot antenna arrays have been usually applied to THz filters with frequency band tunability by their geometry. Normally the amplitude in transmission (reflection) in the collinear alignment case can be varied via rotating the azimuthal angle with a sinusoidal trend, which can limit their utilization and performance only at fixed angle between the alignment of the resonant antennas and incident beam polarization. To pursue a variety of metamaterial uses, here, we present polarization-independent THz filters using variously aligned antenna array (asterisk, chlorophyll, and honeycomb patterns) in such counter-intuitive aspects. Besides, unprecedented multi resonance behaviors were observed in chlorophyll and honeycomb patterns, which can be explained with interferences by adjacent structures. The measured spectra were analyzed by harmonic oscillator model with simplified coupling between slots and their adjacent. (C) 2017 Optical Society of America
Keywords: PLASMON INDUCED TRANSPARENCY; BROAD-BAND; METAL; APERTURE; ARRAYS; NANOANTENNAS; ENHANCEMENT; ABSORPTION; TRANSITION; ABSORBER